Reproductive Toxicity and Recovery Associated With 4-Non-ylphenol Exposure in Juvenile African Catfish (Clarias garepinus) - Sayed, Alaa El-Din H.; Eid, Zainab; Mahmoud, Usama M.; Lee, Jae-Seong; Mekkawy, Imam A. A. (Frontiers in Physiology, 2022)
Although, the effects of 4-non-ylphenol (4-NP) on fish’s reproductive hormones were assessed in several studies using adult models, however, the effect of this endocrine disruptor on immature fish’s reproductive hormones was not addressed commonly. We aimed to study the apoptosis induction, hematotoxicity, reproductive toxicity, and the recovery associated with 4-NP exposure in juvenile African catfish [Clarias garepinus) using some hormones [17β-estradiol (E2), testosterone (T), follicle-stimulating hormone (FSH), and luteinizing hormone (LH)] and gonad histology as biomarkers. The toxic effects of 4-NP have been studied in many animal models, but there is still limited knowledge about the dose-dependent damage caused by 4-NP exposure in juvenile Clarias gariepinus. A healthy juvenile C. gariepinus was categorized into four groups (n = 3/group; three replicates in each group). The first group was the control, and the other three groups were subjected to 4-NP concentrations as 0.1, 0.2, and 0.3 mg/L for 15 days; they were left for a recovery period of another 15 days. The reproductive hormones of C. gariepinus exposed to 4-NP for 15 days exhibited significant variations between the treatment groups and the control (P < 0.05), which were evident in E2 and T-values, whereas FSH, LH, total protein, and lipid peroxidation values showed non-significant differences among all groups at P < 0.05. Such a situation referred to the fact that the 15-day recovery period was insufficient to remove the impacts of 4-NP doses in concern. The trend of dose-dependent increase/decrease was recorded for T, E2, FSH, and LH. The histopathological alterations of 4-NP treated in gonad tissues were recorded in juvenile C. gariepinus, reflecting their sensitivity to 4-NP estrogenic-like effects. Overall, our results investigate that recovery has improved the reproductive toxicity caused by 4-NP in juvenile C. garepinus. Significant variations between the treated groups and the control group (P < 0.05) were evident in hematological parameters except for hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). The parameters exhibiting significance decreased with such increased doses [red blood cells (RBCs), hematocrit (Hct), and white blood cells (WBCs)]. Similar patterns of significant variations toward the increase or decrease were recorded following the 15-day recovery period. Apoptotic frequency in erythrocytes and brain cells has increased significantly with increased 4-NP exposure, indicating that 4-NP caused cytotoxic effects, such as apoptosis in a dose-dependent manner. However, these cellular alterations greatly decreased after the 15-day recovery period.